The Authority of the Banda Aceh City National Narcotics Agency in Combating Narcotics Crimes Among Students from the Perspective of Maqāṣid Al-Sharī‘ah - Alfiyani Alfiyani; Safira Mustaqilla; Yuhasnibar Yuhasnibar; Novi Heryanti; Misran Misran (MAQASIDI: Jurnal Syariah dan Hukum, 2026)
This study examines the authority of the National Narcotics Agency of Banda Aceh City in combating narcotics crimes among students from the perspective of maqasid sharia. Narcotics abuse among students is a serious problem that continues to increase, especially among students aged 17–18 years, and has a negative impact on physical health, psychological conditions, and social life. The research method used is juridical-empirical by combining normative studies of laws and regulations and field data obtained through interviews at the National Narcotics Agency of Banda Aceh City. The results show that BNN has strategic authority in preventing and eradicating narcotics through promotive, preventive, curative, rehabilitative, and repressive efforts. From the perspective of maqasid sharia, narcotics abuse is contrary to the goals of protecting the mind (hifzh al-‘aql), protecting the soul (hifzh al-nafs), and protecting offspring (hifzh al-nasl). The rehabilitation approach implemented by the National Narcotics Agency (BNN) for students who abuse drugs demonstrates an effort to safeguard the welfare and future of the younger generation. Therefore, the Banda Aceh BNN's efforts to combat drug crimes among students are not only in accordance with positive law but also align with the primary objectives of Islamic law from the perspective of the maqasid sharia.